A Gastric Magnetic Foreign Body Incidentally Detected Several Years after Ingestion - Joo, Dong Chan; Lee, Moon Won; Hong, Seung Min; Baek, Dong Hoon; Lee, Bong Eun; Kim, Gwang Ha; Song, Geun Am (The Korean journal of gastroenterology, 2023)
Foreign body ingestion is commonly seen in children. However, occasionally it may also be seen among adults and is often associated with intellectual disability, psychiatric disorders, and alcoholism. Ingestion of a magnetic foreign body may cause complications such as gastrointestinal tract perforation, wherein emergency endoscopic removal of the foreign body is generally required. Here, we report a rare case of a 59-year-old male with an intellectual disability and psychiatric disorder in whom metallic objects in the stomach cavity were accidentally discovered during abdominal CT. Esophagogastroduodenoscopy revealed several metallic objects attached to two magnets, which had been ingested several years before and had remained in the stomach cavity. The magnets and metallic objects were safely removed endoscopically using rat-tooth forceps without complications. KCI Citation Count: 1